RUMAH SAKIT PASIR JUNGHUHN: ARSITEKTUR KHAS BANGUNAN PERKEBUNAN PENINGGALAN ZAMAN BELANDA - Nuralia, Lia (PANALUNGTIK, 2019)
The plantation industry building has an important value in the development of history and architecture in Indonesia, so it is necessary to do research and documentation. One of them is the Pasir Junghuhn Hospital in Purbasari Plantation, which has begun to forget its history and appear physically damaged, so it is feared that it will experience more serious damage and eliminate its historical traces. Archaeological research methods with data collection techniques: surface survey, oral history interviews, literary studies, and colonial archives, provide an explanation of the history and architecture of buildings and the important values contained therein. The results obtained are the building of Pasir Junghuhn Hospital which has historical value, local wisdom, and knowledge of modern western technology and the architectural style of the Hindia Baru typical of the plantation buildings of its era.